2019
DOI: 10.1530/eje-18-0795
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and long-term outcomes in pituitary carcinoma: a cohort study

Abstract: Background Pituitary carcinoma (PC) is an aggressive neuroendocrine tumor diagnosed when a pituitary adenoma (PA) becomes metastatic. PCs are typically resistant to therapy and develop multiple recurrences despite surgery, radiotherapy and chemotherapy. Recently, treatment with temozolomide (TMZ) has shown promising results, although the lack of prospective trials limits assessment of benefit. Methods We describe a single-center multidisciplinary experience in managing PC patients over a 22-year period and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
0
18
0
1
Order By: Relevance
“…Of note, very high Ki-67 index and high mitotic count should alert pathologists to consider other diagnosis than pituitary tumor. Indeed, Ki-67 exceeding 10% are rarely observed in pituitary tumor as shown in a recent cohort [65]. In particular, the diagnosis of null cell adenoma should be considered with caution these cases.…”
Section: Difficult Differential Diagnosismentioning
confidence: 88%
“…Of note, very high Ki-67 index and high mitotic count should alert pathologists to consider other diagnosis than pituitary tumor. Indeed, Ki-67 exceeding 10% are rarely observed in pituitary tumor as shown in a recent cohort [65]. In particular, the diagnosis of null cell adenoma should be considered with caution these cases.…”
Section: Difficult Differential Diagnosismentioning
confidence: 88%
“…Encouraged by these findings, TMZ has been increasingly employed as salvage treatment for APT and PC patients after the failure of standard management with surgical, medical, and radiational treatments (9). TMZ has been demonstrated as a safe therapeutic agent offering a high clinical response rate in patients with APT and PC (10).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, increased expression of p-JAK2 and p-STAT5 was observed in bromocriptine-resistant prolactinoma tissues and cells. In our clinical practice, patients with bromocriptine-resistant prolactinoma usually suffer from hyperprolactinemia (26)(27)(28). Increased serum levels of PRL tend to bind PRLR forming a complex, and further activate the classical PRL/JAK2/STAT5 pathways (8,29,30).…”
Section: Discussionmentioning
confidence: 99%